LOW-PROTEIN DIET IMPAIRS GLUCOSE-INDUCED INSULIN-SECRETION FROM AND CA-45 UPTAKE BY PANCREATIC RAT ISLETS - Carneiro, E. M.; Mello, MAR; Gobatto, C. A.; Boschero, A. C. (Butterworth-heinemann, 1995)
Glucose-induced insulin secretion rom and Ca-45 uptake by isolated pancreatic islets, derived from rats fed with normal (NPD) or low protein diet (LPD), were studied. Insulin secretion from both types of islets in response to increasing concentrations of glucose followed an S-shaped pattern. However, basal secretion observed at substimulatory concentrations of glucose (0-5.6 mM), as well as maximal release, obtained at 16.7 mM or higher glucose concentrations were significantly reduced in islets from LPD. Furthermore, in LPD rat islets, the dose-response curve to glucose was clearly shifted to the right compared with NPD islets, with the half-maximal response occurring at 8.5 and 14.4 mM glucose for NPD and LPD islets, respectively. In islets from NPD rats, the Ca-45 content, after 5 or 90 min in the presence of 8.3 mM glucose, was higher than that observed for islets kept at 2.8 mM glucose and increased further at 16.7 mM glucose. After 5 min of incubation, the Ca-45 uptake by LPD islets in the presence of 8.3 mM glucose was slightly higher than basal values (2.8 mM glucose); however, no further increase in the Ca-45 uptake was noticed at 16.7 mM glucose. In LPD islets a significant increase in Ca-45 uptake over basal values was registered only at 16.7 mM glucose, after 90 min of incubation. These data indicate that the poor secretary response to glucose observed in islets from LPD rats may be related to a defect in the ability of glucose to increase Ca2+ uptake and/or to reduce Ca2+ efflux from beta-cells.
Keywords: PROTEIN DEFICIENCY; ISLETS OF LANGERHANS; INSULIN SECRETION; CA2+ FLUXES